Environmental Trends Due to Arc Welding Activities: Sensitivity of some Typical Workplaces - Shote, A. S.; Aasa, S. A.; Adeyemi, H. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The associated hazards with welding process are recently looked into because of the emission threat or lack or improper use of safety devices in work places relating to welding that could potentially lead to long- or short-term effect on worker and other staying nearby. This article provides data for various air quality parameters such as Total Volatile Organic Compounds (TVOC), Air Quality Index (AQI), Carbon Monoxide (CO), Carbon Dioxide (CO2), and Formaldehyde (HCHO) measured at different locations, North (N), West (W), East (E), and South (S) within Lagos Metropolis. The results of CO and HCHO levels are apparently higher than recommended limits in some locations (East and South) which suggest potential harm for workers as CO is mostly dangerous to health. However, other data suggests that air quality is generally good, as all AQI values are significantly below the break point of 50ppm. Further analysis revealed that at 95% confidence, there is no significant difference in the CO emissions patterns from different workshops as well as from different locations (North, West, East, and South) as Pvalue> 0.05. However, there is difference in CO2 as a result of change in locations as Pvalue (0.014) < 0.05. About 57.6% of the variability in CO2 emissions from various locations can be accounted for due to the variation resulting from change in location. The data thus provides useful information that could enable enforcement of personal protective equipment to ameliorate the situation.